The influence of organisational commitment and job satisfaction on employee corporate social responsibility participation in a financial institution in Gauteng - Nkumane, Mthobisi Roderick (Vaal University of Technology, 2020)
Corporate social responsibility (CSR) has become as an important topic as it has ramifications for practitioners. Corporate social responsibility can change employees’ approaches, demands and behaviours. Organisations can build a sound relation with its employees by promoting CSR in the organisation and inspiring employees to partake in these activities. The primary objective of the study is to explore the relationship between organisational commitment, job satisfaction as well as explore the relationship between job satisfaction and CSR among employees in a financial institution in Gauteng. A quantitative research approach method was used to achieve the primary objective. A structured questionnaire was issued to 250 respondents. Furthermore, composite means and factor analysis were performed to determine the level of organisational commitment, job satisfaction and corporate social responsibility of employees and to establish the underlying factors of the constructs respectively. Additionally, correlation analysis was conducted to establish the strength and direction of the relationship between the factors. Finally, a regression analysis was performed to confirm the predictive relationship between the study constructs. The findings of this study showed a positive correlation between affective commitment, normative commitment and continuance commitment and JS, and also showed a positive correlation between JS and CSR. Based on the findings, it was recommended that the more committed the financial institution employees, the more they are satisfied with their job in the institution. Furthermore, JS contributed positively to CSR, which implied that the more satisfied the employees of the financial institution, the more they feel being part of the CSR activities of the financial institution.
M. Tech. (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Organisational commitment; Job satisfaction; Corporate social responsibility; Dissertations, Academic -- South Africa.; Organizational commitment.; Social responsibility of business -- South Africa.; Job satisfaction -- South Africa.; Financial institutions -- South Africa.